BAURAN PEMASARAN PRODUK BARU PELUMAS FOOD GRADE GREASE BERBAHAN DaSAR MINYAK SAWIT - Ali Maksum; Tri Yanto (Agroindustrial Technology, University of Trunojoyo Madura, 2016)
Grease with food grade specification is essentially required on food processing production activities. The purpose of this study is to develop a new product marketing mix for food grade grease, i.e 1) product priority, 2) pricing priority, 3) distribution priority and 4) advertising priority. This Research was conducted in Sub District Purbalingga and Padamara, Purbalingga regency with respondent SMEs food processing. Analysis of the determination of marketing mix that includes product, price, advertising and distribution using the Analytical Hierarchy Process (AHP). Sampling was purposive random sampling method with a population of 64 SMEs so drawn sample of 20 respondents. Result of the study showed the marketing mix priority which were: (1) advertising priority for the new food grade grease product with an ads that could attract the attention of consumers in order to made the consumers interested, tried, and bought the new food grade lubricating grease products. (2) Price priority for the new food grade grease products which was by determining the moderate prices to compete the competitors' prices while still maintained a high quality. (3) Product priority for new food grade grease product which was producing a qualified product which could withstand the wear of the engine, green colour of the product, a 350 g size packs with a rectangular shape packaging labels. (4) Distribution priority for the new food grade grease product which was a short distribution channels through mobile vendors so that the consumers were able to save costs, and got the product fast and easily